Highly specific chimeric DNA-RNA-guided genome editing with enhanced CRISPR-Cas12a system - Hanseop Kim; Wi-jae Lee; Chan Hyoung Kim; Yeounsun Oh; Lee Wha Gwon; Hyomin Lee; Woojeung Song; Junho K. Hur; Kyung-Seob Lim; Kang Jin Jeong; Ki-Hoan Nam; Young-Suk Won; et al. (Elsevier, 2022)
The clustered regularly interspaced short palindromic repeats (CRISPR)-Cas12a system is composed of a Cas12a effector that acts as a DNA-cleaving endonuclease and a crispr RNA (crRNA) that guides the effector to the target DNA. It is considered a key molecule for inducing target-specific gene editing in various living systems. Here, we improved the efficiency and specificity of the CRISPR-Cas12a system through protein and crRNA engineering. In particular, to optimize the CRISPR-Cas12a system at the molecular level, we used a chimeric DNA-RNA guide chemically similar to crRNA to maximize target sequence specificity. Compared with the wild-type (wt)-Cas12a system, when using enhanced Cas12a system (en-Cas12a), the efficiency and target specificity improved on average by 2.58 and 2.77 times, respectively. In our study, when the chimeric DNA-RNA-guided en-Cas12a effector was used, the gene-editing efficiency and accuracy were simultaneously increased. These findings could contribute to highly accurate genome editing, such as human gene therapy, in the near future.